PEDAGOGICAL REQUIREMENTS FOR THE CONTENT OF FORMING STUDENTS IN THE NATIONAL SPIRIT ON THE BASE OF MUSIC CIRCLES - Kasimjonova Marjona Alisher kizi (Scholars Digest Publishing, 2023)
This article provides detailed information about the pedagogical requirements for the organization of music clubs, pedagogical technologies for improving the pedagogical skills of teachers, and the content of naturalizing students in the national spirit on the basis of music clubs.
Keywords: music, culture, club, education, pedagogical skills, demand, supply, art, interest.